A moment of transformative learning: creating a disorientating dilemma for a health care student using video feedback - James, Deborah M.; Collins, Luke C.; Samoylova, Ekaterina (Sage, 2012)
This study describes a moment during clinical supervision when a student speech and language therapist reported that she had a moment of illumination that changed her trajectory from failing her clinical placement to passing it. The student’s self-report of the moment is provided. The clinical supervision was conducted using video feedback where the student watched successful edited clips of herself interacting with a patient in the university clinic. The clinical supervision where the moment of illumination occurred was recorded and two short extracts of this moment were analysed for evidence of a transformative process using Mezirow’s theory. The content of the student’s speech during the moment of illumination followed the steps and sequence of the transformative learning model. An analysis of the way the speech sounded showed that the moment was characterised by slow speech rate and flat monotonous pitch in both speakers and preceded by the educator modelling stopping and thinking. The use of video footage in student clinical supervision may be used with differential effect. Footage of strengths may be an effective trigger for disorientation and especially when feelings of failure or weakness are most prominent. The way the discussion of the video footage is led by the clinical educator may also support deep reflection.